Improving the fracture toughness properties of epoxy using graphene nanoplatelets at low filler content - Nadiim Domun (Taylor & Francis Group, 2017)
This paper reports improvement in the fracture properties of epoxy nanocomposites using plasma functionalized graphene nanoplatelets (f-GNP) at low filler content. Various mechanical tests were performed on a series of f-GNP/epoxy at low nanofiller loading to assess the effect of the nanofiller on mechanical properties. Most importantly, a significant enhancement in fracture toughness is achieved without compromising the tensile and thermal properties of the nanocomposites. The fracture toughness of neat epoxy resin was increased by over 50% with the incorporation of 0.25 wt% f-GNP loading, obtaining a value of 245 J m−2, while the neat epoxy indicated a value of 162 J m−2. The glass transition temperature (Tg) and coefficient of thermal expansion (CTE) both showed a slight increase of 3% and 2%, respectively, both at 1 wt% f-GNP loading. These enhancements are competitive with current literature results on nanocomposites, but at significantly lower filler content. We therefore demonstrate that f-GNPs are capable of providing effective toughening of epoxy resins, while maintaining other tensile and thermal properties.